Barriers and Facilitators in Accessing HIV Prevention Services for Men Having Sex with Men (MSM): A Comprehensive Analysis - Felix Sanni; Roger Abang; Godwin Emmanuel; Abiye Kalaiwo; Olugbemi Motilewa; Paul Amechi; Paul Umoh; Bartholomew Boniface Ochonye (Babcock University Medical Journal)
Objectives: This study explores MSM’s perspective on HIV prevention needs, barriers, facilitators, and retention strategies in prevention programs.